Malaria in Sri Lanka: Current knowledge on transmission and control - Konradsen, Flemming; Amerasinghe, Felix P.; Hoek, Wim van der; Amerasinghe, Priyanie H. (International Water Management Institute, 2000)
Malaria is a major health problem in Sri Lanka. Over the years a large pool of knowledge has accumulated on malaria in Sri Lanka. This book reviews a broad range of published literature of relevance for a description of malaria in Sri Lanka, including control aspects of the disease. Based on the literature examined, a general overview of the status of research in Sri Lanka is given, and areas where knowledge is lacking and further studies are required are identified.